Transaksi valuta asing sarf dalam konsepsi fikih muâamalah - Suryani, Suryani (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2013)
Buying and selling foreign currencies (as-Sa{ rf) basically arises because of the need for conversion of onecurrency to another currency in international trade traffic that will encourage the supply and demand forforeign exchange, which in turn will bring up the sale and purchase of foreign currency in the foreignexchange market.The practice of buying and selling foreign currency according to fiqh muâam> alah is permitted if it is doneby an agreement between the two sides and in cash (spot) and it could not be included the addition ofa similar item like gold with gold or silver with silver.